The summer house [compact disc, unabridged] - Patterson, James, 1947-; DuBois, Brendan (Hachette Audio, 2020)
Sullivan County, Georgia, belongs to Sheriff Emma Williams. But not when Army Rangers posted to the local base are implicated in a major crime. To an elite team of investigators led by Major Jeremiah Cook, the physical evidence Williams swears by presents clues to an entirely different story. The small-town sheriff has never worked a multiple homicide, and Cook knows it. Unless he can convince the locals that the recent crimes are part of a larger mystery, this outsider may never unlock the century of secrets hidden inside The Summer House.